Early response to upfront neoadjuvant chemotherapy (CAPOX) alone in low- and intermediate-risk rectal cancer: a single-arm phase II trial. Issue 1 (18th November 2021) - Deng, Xiangbing; Wu, Qingbin; Bi, Liang; Yu, Yongyang; Huang, Shuo; He, Du; Wu, Bing; Gou, Hongfeng; Meng, Wenjian; Qiu, Meng; He, Yazhou; Wang, Ziqiang
Abstract: Background: With local recurrence of rectal cancer continuing to decrease, distant recurrence is becoming a major concern, especially for patients with low- and intermediate-risk stage II/III rectal cancer. Therefore, a new treatment strategy is warranted for these patients. This single-arm phase II trial aimed to assess the effect of neoadjuvant chemotherapy (NCT) in low- and intermediate-risk stage II/III rectal cancer and explore candidate radiological and clinical parameters for early prediction of tumour response after two cycles of CAPOX. Methods: Patients with mid–low stage II/III rectal cancer with low and intermediate risk were examined. The primary outcome was defined as a clinicopathological response by integrating tumour longitudinal length reduction (TLLR) on MRI into pathological tumour regression grade (TRG). After completing NCT, patients with TRG0–2 and TRG3 with a TLLR rate greater than 30 per cent were considered to be responders. Secondary outcomes included pathological complete response (pCR), adverse events and local and distant recurrence. Results: This study enrolled 61 eligible patients. No patient was converted to neoadjuvant chemoradiotherapy owing to tumour progression. The clinicopathological response and pCR rates were 78.7 and 21.3 per cent respectively. After two cycles of CAPOX, TLLR, TRG on MRI, and mucosal lesion regression grade on endoscopy had potential discriminative ability (area under the curve greater than 0.7) for predicting both clinicopathological and pathological response. Conclusion: NCT alone achieves good tumour response rates in patients with low- and intermediate-risk stage II/III rectal cancer, and predicting tumour response to NCT is feasible at an early treatment phase. Registration number: NCT03666442 (http://www.clinicaltrials.gov ). Abstract : Neoadjuvant chemotherapy alone achieves desirable tumour response rates in low- and intermediate-risk stage II/III rectal cancer. Tumour longitudinal length reduction, tumour regression grade on MRI, and mucosa lesion regression grade on endoscopy are promising for early prediction of both clinicopathological and pathological response.